The evolution of a manufacturing system at Toyota - Fujimoto, Takahiro (Oxford University Press, 1999)
The book traces the development of Toyota's manufacturing system, analyzing its principles, processes, and organizational innovations. Fujimoto highlights how Toyota's approach to production evolved into a lean system that integrates technology, management, and culture to achieve efficiency and competitiveness